Concepções dos estudantes de uma escola pública do distrito de Santa Luzia do Cariri – PB sobre as adaptações das plantas da Caatinga à seca - Lima, Klebson Cordeiro da Silva (2024)
The Caatinga Biome presents a functional spectrum that includes various effects/responses to the environmental filters to which it is subject. These traits range from anatomical, morphological, physiological and structural characteristics to the responses between plant-environment interactions. The vegetation of the Paraíba cariri presents several adaptations to drought and will serve perfectly to analyze students' conception of the Caatinga, using teaching strategies through investigative activities that enable meaningful learning. The present study aimed to improve the conception of students at a state public school about the adaptations of caatinga plants to drought. Based on the experiences of students connecting the field class. This research was carried out in a state public school, located in the district of Santa Luzia do Cariri (Paraíba), with 60 students from the 2nd year of high school as research subjects. The research followed the assumptions of the National Common Curricular Base (BNCC) and the Common Curricular Parameters (PCN), with the purpose of expanding students' knowledge about local biodiversity (Cariri Paraíba). In this research, an investigative didactic sequence was carried out, where the final product was a didactic guide based on a field class in Serra do Jatobá, taking into account the region's vegetation and its adaptations to drought. This guide aims to help biology teachers combat students' botanical imperception using native specimens from Paraíba's Cariri, focusing on morphophysiological characteristics and their potential for ethnobotanical studies. The field class brought students an improvement in the visibility of this biome and proved to be an important tool for teaching biology. To create the product, if necessary, an assessment was made of the students' prior knowledge based on a survey questionnaire, analysis of the students' perception based on drawings and records (image capture) of the field class, and debates on the species of plants in the region, making this biome a learning environment. Considering that this research aroused greater interest in the discipline, as well as contributing to the improvement of teaching – learning for students, by improving their conceptions about vegetation based on what is around them. It is concluded that the use of active methodologies, teaching through investigation, student leadership, are essential in the study of biology, especially in the discipline of botany, as they helped to combat the botanical imperception of students who are inserted in the Caatinga, and expect – teachers are expected to be multipliers of the product generated here.